SecurityTAG’S - Kiran Kumar, Boddepalli; Swaroopa, Korla (International Journal of Computer Sciences and Engineering, 2022)
In this paper, initially we describe the present antivirus in aspects like –memory[1] they are consuming, and how efficiently they are protecting the system. In the next section of this paper we briefly discuss the design methodologies that are practiced presently, their drawbacks and limitations. Finally we describe an effective design methodology which uses SecurityTAG to protect the system. SecurityTAG is generated by the SecurityTAG generator which takes some parameters as inputs and gives the SecurityTAG as the output. This gives better protection against any virus and detection of infected files is very easy and effective.